The mouse oral carcinoma (MOC) model: A 10-year retrospective on model development and head and neck cancer investigations. (September 2022) - Kono, Michihisa; Saito, Shin; Egloff, Ann Marie; Allen, Clint T.; Uppaluri, Ravindra
Highlights: The mouse oral carcinoma (MOC) cell line models were developed from 7, 12-dimethylbenz(a) anthracene (DMBA)-induced primary mouse oral squamous cell cancers over 10 years ago. MOC models have been used in numerous head and neck squamous cell cancer (HNSCC) investigations, including studies on oral cancer tumor biology, host anti-tumor immune responses and therapeutic approach. Three cell lines (MOC1, 2, and 22) have key driver mutations of human HNSCC and different tumor biological characteristics, therapeutic sensitivity, and immune response Understanding and integrating MOC model with human tumor biology may facilitate optimization of various therapeutic approaches and clinical translation for HNSCCs. Abstract: Preclinical models of cancer have long been paramount to understanding tumor development and advancing the treatment of cancer. Creating preclinical models that mimic the complexity and heterogeneity of human tumors is a key challenge in the advancement of cancer therapy. About ten years ago, we created the mouse oral carcinoma (MOC) cell line models that were derived from 7, 12-dimethylbenz(a) anthracene (DMBA)-induced mouse oral squamous cell cancers. This model has been used in numerous investigations, including studies on tumor biology and therapeutics. We have seen remarkable progress in cancer immunology in recent years, and these cell lines, which are syngeneic to C57BL/6 background, have also been used to study the anti-tumor immune response. Herein, we aim to review the MOC model from its development and characterization to its use in non-immunological and immunological preclinical head and neck squamous cell carcinoma (HNSCC) studies. Integrating and refining these MOC model studies and extending findings to other systems will provide crucial insights for translational approaches aimed at improving head and neck cancer treatment.